2015
DOI: 10.1002/prot.24738
|View full text |Cite
|
Sign up to set email alerts
|

The structure ofS.lividansacetoacetyl-CoA synthetase shows a novel interaction between the C-terminal extension and the N-terminal domain

Abstract: The AMP-forming acyl-CoA synthetase enzymes catalyze a two-step reaction that involves the initial formation of an acyl adenylate that reacts in a second partial reaction to form a thioester between the acyl substrate and CoA. These enzymes utilize a Domain Alternation catalytic mechanism, whereby a ~110 residue C-terminal domain rotates by 140° to form distinct catalytic conformations for the two partial reactions. The structure of an acetoacetyl-CoA synthetase (AacS) is presented that illustrates a novel asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…AacS is present in all domains of life, and this work provided the first example of the regulation of its activity by acetylation. Recently, the structure of SlAacS was reported, which provided for the first time an ordered view of the 30-residue extension of the C terminus of this type of enzyme, and it was suggested that such an extension may interact with catalytic residues of the N-terminal domain (189). A comparison of SlAcs and SlAacS would provide valuable insights into the determinants that make AMP-forming acyl-CoA synthetases good substrates for the SlPatA enzyme.…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
“…AacS is present in all domains of life, and this work provided the first example of the regulation of its activity by acetylation. Recently, the structure of SlAacS was reported, which provided for the first time an ordered view of the 30-residue extension of the C terminus of this type of enzyme, and it was suggested that such an extension may interact with catalytic residues of the N-terminal domain (189). A comparison of SlAcs and SlAacS would provide valuable insights into the determinants that make AMP-forming acyl-CoA synthetases good substrates for the SlPatA enzyme.…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
“…It has been demonstrated for several members of the ANL superfamily that the C‐terminal domain adopts different conformational states during the catalytic cycle through a mechanism called “domain alternation”, with a rotation of up to 140° around a conserved hinge residue . This flexibility is also reflected in elevated B ‐factors and disordered parts for the C‐terminal domain, which can be seen in the crystal structures of the acetoacetyl‐CoA ligase Sl Acs, the anthranilate‐CoA ligase AuaEII, or the o ‐succinylbenzoyl‐CoA ligase MenE, for example …”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33] This flexibility is also reflected in elevated B-factors andd isordered parts for the C-terminal domain, which can be seen in the crystal structures of the acetoacetyl-CoA ligase SlAcs, the anthranilate-CoA ligase AuaEII, or the osuccinylbenzoyl-CoA ligase MenE, for example. [54][55][56] Because this mobility and flexibility might impede crystallization, we decided to use aP qsA construct lacking the whole Cterminald omain (PqsA NTD ), ending in the hinge residue (D399, Figure1Aand Figure S1 in the Supporting Information). Similar truncations have already been successfully employed in the crystallization of other ANL enzymes.…”
Section: Crystallization Of Pqsa Ntdmentioning
confidence: 99%
“…This is followed by removal of the excess of peptide linker. Subsequently, the first protein (P1, green) of the fusion protein, exhibiting a C-terminal LPETG motif, is ligated to the N-terminus of the fusion intermediate linker-protein from step (2) using sortase-mediated ligation (3). Finally, the fusion protein is purified form the reaction mixture by dual affinity chromatography (4).…”
Section: Design Of Native Chemical Ligation and Sortase-mediated Ligamentioning
confidence: 99%
“…Some examples that are of great interest to study are the multi‐modular biosynthetic machineries comprising the polyketide synthases and non‐ribosomal peptide synthetases because of the many high value compounds produced by these assembly lines . The assembly modules of these synthases are themselves divided into many different domains, which are attached by protein linkers that appear to be highly important for their activity . The activity of such machineries depends upon domain‐domain interactions in both cis and trans .…”
Section: Introductionmentioning
confidence: 99%